Results of open heart surgery in Jehovah’s Witness patients. Single centre experience - Juraszek, Andrzej; Kołsut, Piotr; Szymański, Jarosław; Kuriata, Jarosław; Kuśmierski, Krzysztof; Sitkowska-Rysiak, Ewa; Jasińska, Małgorzata; Kuśmierczyk, Mariusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
Aim : Evaluation the results in patients from the religious community of Jehovah’s Witness (JW) undergoing open heart surgery at our institution. Material and methods : Between September 2011 and March 2015, 21 patients with a religious background of the JW church underwent open heart surgery at our institution performed by the same surgical team. Mean age was 68.43 ±8.93 years. There were 13 (61.9%) female patients. Recombinant human erythropoietin was administered to every patient with a hemoglobin value < 12.0 g/dl. Nine patients undergoing isolated coronary artery revascularization were operated on without cardiopulmonary bypass. Seven patients underwent combined surgery and 5 patients underwent aortic valve replacement via ministernotomy. The mean follow-up time was 16.45 ±11.09 months (range: 1.67–44.3 months). Results : Mean baseline hematocrit serum level was 40.15 ±3.34% (range: 34.5–46.1%). Perioperatively the hematocrit serum levels decreased to the mean level of 29.89 ±4.31% (range: 21.4–36.3%). The mean hematocrit value at discharge was 30.85 ±3.59% (range: 23.5–38.4%). One death was observed in the perioperative period. Five (24%) patients suffered from sternum wound infection requiring vacuum-assisted therapy. During the follow-up period 1 patient died due to a non-cardiac related cause. Conclusions : After careful preoperative preparation the results of open heart surgery in JW were very good, including combined procedures. The decrease of hematocrit serum levels significantly characterizing the postoperative period was highly acceptable in this series. Nevertheless, the number of sternum wound infections was a limiting factor for prompt postoperative recovery.